Developing confidence in a learner through peer-led team learning strategy: Curbing the menace of examination malpractice in science - Njoku, Martha Ijok Adibe; Shedrack, Tamunoiyowuna (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
This paper considered examination malpractice in tertiary institutions, the consequential effect of indulgence in this menace and basic factors influencing the continuous occurrence. Special attention was directed to an innovative learning strategy that can effectively control students' involvement in examination malpractice. Details on how to use this innovative peer-led team learning strategy were presented. The paper concluded by suggesting that a peer-led team learning strategy be infused into the teaching practice of the university to curb the menace of examination malpractice and produce self-confident graduates with relevant skills to fit properly into the global workforce